2010
DOI: 10.1002/cncr.24793
|View full text |Cite
|
Sign up to set email alerts
|

Improved efficacy of α‐particle–targeted radiation therapy

Abstract: BACKGROUND Human epidermal growth factor receptor–2 (HER-2) and tumor-associated glycoprotein 72 (TAG-72) have proven to be excellent molecular targets for cancer imaging and therapy. Trastuzumab, which binds to HER-2, is effective in the treatment of disseminated intraperitoneal disease when labeled with 213Bi or 212Pb. 213Bi-humanized CC49 monoclonal antibody (HuCC49ΔCH2), which binds to TAG-72, inhibits the growth of subcutaneous xenografts. A next logical step to improve therapeutic benefit would be to tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…There is, however, growing interest in the development of therapies using antibodies labeled with α -particle-emitting radionuclides (Miederer et al 2008, Sgouros 2008, Boskovitz et al 2009, Song et al 2009, Milenic et al 2010, McDevitt et al 2001). Alpha particles have a relatively short range in tissue ( < 90 μ m) and a high linear energy transfer (LET), depositing large amounts of energy per unit track length.…”
Section: Introductionmentioning
confidence: 99%
“…There is, however, growing interest in the development of therapies using antibodies labeled with α -particle-emitting radionuclides (Miederer et al 2008, Sgouros 2008, Boskovitz et al 2009, Song et al 2009, Milenic et al 2010, McDevitt et al 2001). Alpha particles have a relatively short range in tissue ( < 90 μ m) and a high linear energy transfer (LET), depositing large amounts of energy per unit track length.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the anti-TAG-72 antibody was used as a radioimmunotherapeutic agent to treat ovarian cancer (37). Moreover, several nanoparticles conjugated with the anti-TAG-72 antibody were also used as targeting agents for radioimmunotherapy and tumor imaging (13, 38). The CC49 mAb recognizes the sialyl-Tn and sialyl-T epitopes, which are disaccharide carbohydrate antigens present on TAG-72.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor-associated glycoprotein (TAG)-72 is a membrane protein complex of approximately 220–400 kDa (13). It was demonstrated that TAG-72 is overexpressed in a number of human tumors such as colon cancer, ductal breast cancer, lung cancer, epithelial ovarian cancer, hepatocellular carcinoma, and oral cancer, but is not expressed by most normal tissues (14–18).…”
Section: Introductionmentioning
confidence: 99%
“…Adenovirus carrying fused CC49, a humanized anti-TAG-72 monoclonal antibody, can transfer a target gene selectively to ovarian carcinoma cells without Coxsackie-adenovirus receptor and significantly decreased adenovirus-mediated toxicity was observed [26]. Moreover, several nanoparticles conjugated with the anti-TAG-72 antibody, as well as a fluorophore-labeled anti-TAG-72 antibody have also been used as targeting agents for radioimmunotherapy and tumor imaging [2730]. Because TAG-72 is specifically expressed in colon carcinoma tissues, we attempted to target colon carcinoma using 3E8-mEndo in an effort to improve the anti-tumor efficacy of this fusion protein.…”
Section: Discussionmentioning
confidence: 99%